2015
DOI: 10.1364/oe.23.020647
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observation of multiple dispersive waves emitted by multiple mid-infrared solitons in a birefringence tellurite microstuctured optical fiber

Abstract: We experimentally demonstrate multiple dispersive waves (DWs) emitted by multiple mid-infrared solitons in a birefringence tellurite microstuctured optical fiber (BTMOF). To the best of our knowledge, this is the first demonstration of multiple DWs in the non-silica fibers. By using a pulse of ~80 MHz and ~200 fs emitted from an optical parametric oscillator (OPO) as the pump source, DWs and solitons are investigated on the fast and slow axes of the BTMOF at the pump wavelength of ~1800 nm. With the average pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…It is reported that plasma also plays a role of inducing fission of higher-order solitons in the gas-filled Kagome HC-PCF. [38] Furthermore, in the investigation of multiple DW generation, [39] phasematching is also discussed and there appears a condition of wavelength shifting on which some of the cal-culated points do not match with the measurements exactly. We preliminary assume that this phenomenon is due to the interplay between multiple DWs.…”
Section: ) and 2(h)mentioning
confidence: 99%
“…It is reported that plasma also plays a role of inducing fission of higher-order solitons in the gas-filled Kagome HC-PCF. [38] Furthermore, in the investigation of multiple DW generation, [39] phasematching is also discussed and there appears a condition of wavelength shifting on which some of the cal-culated points do not match with the measurements exactly. We preliminary assume that this phenomenon is due to the interplay between multiple DWs.…”
Section: ) and 2(h)mentioning
confidence: 99%
“…The recent researches on MOFs focus on soft glasses like fluoride, tellurite and chalcogenide [5]- [7], and the fabricated optical fibers are called soft glass MOFs. Due to higher refractive index, higher nonlinearity and wider transmission ranges, the soft glass MOFs are greatly advantageous for soliton self-frequency shift [8], [9], supercontinuum generation [11]- [13], and they have been widely used in sensing field for gas molecular, biological molecular concentration, temperature and so on. In 2015, Dai et al [15] presented a prototype mid-infrared sensor system using the chalcogenide optical fiber for the determination of combustion pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of five stable individual solitons was due to the SRS properties of the tellurite MOF with a higher Raman gain coefficient, a wider Raman shift, and a multiple-peak Raman gain spectrum. 20) This suggests that the increased pump power redistributed once again. Through the experiment, we conclude that from ∼30 to 220 mW, the evolution of the MIR higher-order soliton fission was determined by the distribution of the average pump power.…”
mentioning
confidence: 99%
“…13,14) Up to now, numerous works have been carried out concerning the higher-order soliton fission in various optical fibers. [15][16][17][18][19][20][21] In this study, we demonstrated the evolution of the midinfrared (MIR) higher-order soliton fission in a tapered tellurite microstructured optical fiber (TMOF). The pump wavelength was ∼1800 nm, which originated from an optical parametric oscillator (OPO).…”
mentioning
confidence: 99%